Passive Mechanical Heat/Mass Exchange Enhancement by Semi-Confined Laminar Parallel Wall Jets - Granados-Ortiz, Francisco-Javier; Ortega-Casanova, Joaquín (Elsevier, 2021)
Many different approaches have been investigated in the literature to achieve efficient heat and mass exchangers in applications in several fields such as mechanical, aeronautical or biomedical engineering. Some of these engineering devices need to efficiently mix two fluids at different temperature or concentrations, achieving a decent mixing at a low power cost, and using passive mechanical elements if possible. This paper introduces and analyses numerically the novel application of two parallel wall jets to enhance mixing by vortex shedding induced mechanically. The numerical approach is the non-uniform finite difference approximation, used for the first time in the study of mixing mechanics. The parallel wall jets are constrained within a channel, which can be a simple and passive easily manufactured machine with high potential as scalable laminar mixing device. Different wall jet geometries and Reynolds numbers have been tested with a verified&validated CFD code based on non-uniform finite difference approximation. This analysis allowed to predict configurations that lead to unsteady oscillatory motion. In general, it has been observed that for a range of laminar wall jets, a small channel ratio seems a very efficient option for heat/mass transfer, thanks to the intense oscillation generated in the flow downstream, which enhances mixing with low power requirement.
Keywords: Ingeniería mecánica; CFD; Heat transfer; Mass transfer; Mixing machines; Mechanical engineering